Validation Of The Cadmium Analysis Method (Cd) by Atomic Absorption Spectrophotometry in Traditional Scrub - Suhardiana, Eddy; Endah, Srie Rezeki Nur (Jurnal MIDPRO, 2020)
Scrub is a type of cosmetics that has been widely used for skin care. However, many women do not realize that among the cosmetic products, including the scrubs they usually use, they may contain dangerous ingredients such as heavy metals. The use of scrubs, especially traditional scrubs that contain ingredients from nature, allows heavy metal contamination. This study aims to validate the analysis method of cadmium heavy metal content in traditional scrubs in the city of Tasikmalaya. Sample preparation used the wet digestion method using HNO3: H2O2 (3: 1). Cadmium was analyzed by Atomic Absorption Spectrophotometry at a specific wavelength of 283.3 nm, respectively. After obtaining the optimum digestion process and tools, the cadmium method was validated with Atomic Absorption Spectrophotometry (AAS) which included linearity tests, detection limits, quantification limits, precision and accuracy. The results of the validation of the analysis method obtained a linear calibration curve in the concentration range of 1-8 ppm with a linear regression equation y = 0.1237x + 0.0247, the value of the correlation coefficient = 0.9982. The detection and quantitation limits were 0.63 ppm and 2.11 ppm. Intra-day and inter-day precision is SBR <2%. The retrieval or accuracy obtained is 101.64 - 105.49%.Â